#### Answer

{(3,2)}

#### Work Step by Step

x+2y=7
x+2y-2y=7-2y
x=7-2y
Plug this value for x into the other equation
2x+y=8
2(7-2y)+y=8
14-4y+y=8
14-3y=8
14-14-3y=8-14
-3y=-6
y=$\frac{-6}{-3}$
y=2
Therefore the solution is {(3,2)}

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

{(3,2)}

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.